Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 8 - Radical Functions - 8.5 Complex Numbers - 8.5 Exercises - Page 663: 53



Work Step by Step

$(7+6i)(7+6i)$ =$7(7+6i)+6i(7+6i)$ =$49+42i+42i+36i^{2}$ =$49+84i+36(-1)$ =$49-36+84i$ =$13+84i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.